Quasi-Exact Coulomb Dynamics of n Charges n-1 of Which Are Equal - Wolodymyr Skrypnik (Advances in Mathematical Physics)
For n≥3 point charges n-1 of which are negative and equal quasi-exact periodic solutions of their Coulomb equation of motion are found. These solutions describe a motion of the negative charges around a coordinate axis in such a way that their coordinates coincide with vertices of a regular polygon in planes perpendicular to the axis along which the positive charge moves. The Weinstein and center Lyapunov theorems are utilized.